Acupoint stimulation for postpartum breastfeeding insufficiency: a systematic review and meta-analysis - Ya-Ching Chang; Yi-An Wang; Zi-Yu Chang; Jian-An Liao (Systematic Reviews)
Abstract Background Insufficient lactation, known as hypogalactia, is an important reason for weaning. To date, no effective methods have been established to increase lactation volume. With the advantages of low cost and convenience, acupoint stimulation—defined as any stimulation applied at acupoints—is a promising option. Objectives The aim of this systematic review was to evaluate the effectiveness of acupoint stimulation for postpartum breastfeeding insufficiency. Methods A systematic search of seven databases (PubMed, MEDLINE, Embase, Cochrane, CNKI, Airiti Library, ClinicalTrials.gov) was performed from their inception dates to September 30, 2023. Randomized trials were included. The inclusion criteria of the intervention included acupuncture, acupressure (including tuina and massage), electroacupuncture, laser stimulation, catgut embedding, and auriculotherapy. The primary outcomes were the amount of lactation and the level of prolactin. Secondary outcomes were colostrum time and adverse effects. The risks of bias were assessed using RoB 2.0. Results Twenty-four studies involving 3214 participants were included. When compared to the control group, the experimental group exhibited improved volume of milk production (MD = 81.30; 95% CI = 58.94–103.67) and higher prolactin levels (MD = 41.90, 95% CI = 28.57–55.22). Colostrum time was shorter in the control group ([MD = − 7.26; 95% CI = − 10.69 to − 3.83] for continuous data; [RR = 1.70; 95% CI = 1.38–2.08] for dichotomous data). Adverse effects were reported in only one trial, which included three cases of fear of acupuncture and one case of hypotension. Conclusions Acupoint stimulation may have beneficial effects on postpartum breastfeeding insufficiency. However, the results should be interpreted with caution because of the presence of risks of bias and heterogeneity among studies.